GenderBased Differences among the Students of Tabriz University of Medical Sciences in Academic HelpSeeking Styles and Procrastination - Ramin Habibi-Kaleybar (Kerman University of Medical Sciences, 2016)
Background & Objective: Procrastination is one of the effective factors that reduce students academic performance The rate of procrastination and helpseeking styles may be different in male and female students and this can affect their academic performance So this research aimed to determine the differences among male and female students of Tabriz University of Medical Sciences Iran in academic procrastination and academic helpseeking styles Methods: In this descriptive study research participants included 392 students (234 female and 158 male) of Tabriz University of Medical Sciences in the academic year of 201415 who were selected using stratified random sampling method Procrastination Assessment Scale and academic helpseeking styles questionnaire were performed by the participants Validity and reliability of questionnaires were approved The gathered data were analyzed via SPSS software using MANOVA test Results: There were significant differences among the male and female students regarding procrastination and academic helpseeking style components The mean scores of readiness for the exams and providing the midterm report components (1448) was higher in female students In addition female university students used autonomous helpseeking style (1629) while male university students used avoidant helpseeking style (920) Conclusion: Totally higher or lower scores in students procrastination and academic helpseeking style components depends on factors such as parents attitude or insight to parenting styles This research has implications for teachers educators and consultants which can be used for improving the university students achievement